Assessment of Nutritional and Depression Status in Free-Living Elderly in Tabriz, Northwest Iran - Payahoo, Laleh (Tabriz University of Medical Sciences, 2013)
Background: Malnutrition and depression are the common health problems in elderly population. Poor nutrition might have a strong effect on the incidence of depression. The aims of this study were to assess the nutritional and depression status and the possibly relationship between these variables in the urban free-living elderly in Tabriz, northwestern Iran. Methods: This cross-sectional study was carried out on 184 elderly people (male=97; female=87) with age 60 years or elder in 2012. All subjects entered to the study voluntarily from those attending to daily care centers for elderly people. Mini Nutritional Assessment (MNA) tool and Geriatric Depression Score (GDS) were used to evaluate nutritional status and depression scores, respectively. Continuous variables were expressed as mean ± standard deviation (SD) and qualitative data were presented as frequency (percent). Spearman’s correlation was employed to determine the relationship between variables. Results:Up to 50% of subjects had poor nutrition status. About 14% of elderly people had serve depression and 28.3% had mild depression. There was a positive significant correlation between MNA and GDS tests in both gender (r=0.416; P<0.001). Conclusion: There was no acceptable level of nutritional status and mental health in the elderly people. Further studies are needed to evaluate the other factors that can effect on the quality of life in this population.